Student Interest in Learning the SKI Course Material: How is it Related to Self-Confidence among PAI Students? - Zulfikar, Robi; Sunarto, Sunarto; Baharudin, Baharudin; Susilawati, Beti; Latifah, Sri; Azizah, Nurul (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research aims to examine the relationship between self-confidence and interest in learning in the 5th semester of Islamic Religious Education (PAI) students at Raden Intan Lampung State Islamic University in the History of Islamic Culture course for the 2024/2025 academic year. This research uses a quantitative approach with ex-post facto methods. The research sample consisted of 81 students selected using simple random sampling techniques from a population of 414 students. Data collection was carried out using a Likert scale questionnaire, which had been tested for validity and reliability. Data analysis was carried out using IBM SPSS Statistics 23, including normality, homogeneity, linearity, heteroscedasticity tests, as well as hypothesis tests (t test, F test, and coefficient of determination). The research results show that self-confidence has a significant and linear relationship with interest in learning, with a significance value in the F test of 0.261 and in the t test of 0.000. The coefficient of determination shows that self-confidence influences interest in learning by 10.7%, while the rest is influenced by other factors. This research confirms the importance of self-confidence in increasing students’ interest in learning. Lecturers are advised to use learning methods that support the development of self-confidence, such as interactive discussions and guidance programs that motivate active involvement in learning.